Alopecic and aseptic nodules of the scalp: A new case with a systematic review of the literature - Bellinato, Francesco (Clin Case Rep, 2021)
Alopecic and aseptic nodule of the scalp/Pseudocyst of the scalp is a rare but probably underdiagnosed nonscarring alopecia with good prognosis and doxycycline is a safe and effective option treatment.